2017
DOI: 10.1021/acsami.6b16158
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Uranium over NH2-Functionalized Ordered Silica in Aqueous Solutions

Abstract: The aim of this work was to obtain an in-depth understanding of the U(VI) adsorption mechanism over amino-functionalized mesoporous silica SBA-15 and highlights its high efficiency in aqueous media for U(VI) removal and preconcentration. The samples were synthesized and functionalized by both grafting and co-condensation methods, using different alkyl-substituted amine groups and were characterized using X-ray diffraction, N physisorption, Fourier transform infrared spectroscopy, and elemental C-H-N-S analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 66 publications
2
41
0
Order By: Relevance
“…Other parameters of the Langmuir formalism interpreting experimental data are reported in Table S2. The results confirm also the higher capacity of HMSNs‐NH 2 with respect to HMSNs‐SA, which could be ascribed to the higher organic moieties density and reduced steric hindrance in comparison of the two functional groups …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Other parameters of the Langmuir formalism interpreting experimental data are reported in Table S2. The results confirm also the higher capacity of HMSNs‐NH 2 with respect to HMSNs‐SA, which could be ascribed to the higher organic moieties density and reduced steric hindrance in comparison of the two functional groups …”
Section: Resultssupporting
confidence: 87%
“…Desorption and reusability . The pH dependency of the adsorption of uranyl ions onto HMSNs‐NH 2 and HMSNs‐SA as well as the stability of these functionalized mesoporous silica under acidic condition give the possibility of the removal of adsorbed ions by controlling the acidity of the elution solution . The U(VI) loaded material can be eluted by 0.01 M nitric acid easily and the removed U(VI) was found to be 98 ± 1% by both functional adsorbents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huynh et al reported 250 mg U(VI) uptake per g of a sorbent composed of amine functionalized mesoporous silica (SBA-15). Both IR (v 3 = 909 cm −1 ) and Raman (v 1 = 827 cm −1 ) spectroscopies suggested inner sphere coordination with the surface amines of the sorbent [239]. Amidoxime-containing materials have been shown to selectively uptake U(VI).…”
Section: Surface Speciation Studied By Ir and Raman Spectroscopiesmentioning
confidence: 99%
“…For instance, considering the characteristic of metal ion sorption, recent e®orts have been devoted to synthesize functional SBA-15 with organic ligands containing N, O, S and P elements to selectively interact with actinide ions. Speci¯cally, dihydroimidazole, 19 amine groups, 20 phosphonate, 21 Schi® base 22 and others 23 are proposed to improve the surface a±nity and selectivity of SBA-15 to U(VI). Moreover, the synthesis of SBA-15 with various mesostructures and their structure-dependent sorption behaviors has also been reported.…”
Section: Introductionmentioning
confidence: 99%